Educational leadership: the case of graduate students in Mexico - Díaz Gómez, Eduardo Raúl (My University, 2019)
This study was conducted by using one leadership questionnaire to collect self-evaluations from graduate students. Exploratory factor analysis revealed that the Leadership Practices Inventory measures two leadership constructs consistent with transformational leadership theory: charismatic and adaptive leadership. The study was conducted by surveying 309 graduate students in Mexico. Results suggest that Master of Education students scored higher than Master of Business Administration students in the charismatic leadership factor. No statistically significant differences were identified between those two groups for the adaptive leadership factor. This finding may help educational leaders develop assessment plans designed to measure leadership self-efficacy in their students while facilitating a data-driven approach for improvement of curriculum and teaching. Moreover, this study reinforces the claims of researchers who noted that models and questionnaires of transformational leadership are based on overlapping dimensions.
Revista innovación educativa del instituto politécnico nacional
Keywords: Transformational; Leadership; Learning assessment; Graduate education; Mexico; Sistemas